Instrumentos de controle da despesa com pessoal inativo e pensionista de estados, municípios e do Distrito Federal - Marcelo Abi-Ramia Caetano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The aim of this paper is to point out reforms on the payroll of pensioners and survivors which are possible to be implemented by states, municipalities and the Federal District. All proposals are entirely consistent with that established by the Constitution and by federal laws. In that sense, they are policy options possible to be implemented by subnational entities of the federation within the structure of current federal legislation. There will be no proposition of actions that need to change federal legislation for its effective implementation. The set of possible actions is divided into three major groups: administrative, structural and parametric reforms.
Keywords: H55; H76; 330